Pater's Portraits Mythic Pattern in the Fiction of Walter Pater - Monsman, Gerald Cornelius (Johns Hopkins University Press, 2019)
Originally published in 1967. Monsman undertakes a comprehensive critical analysis of Walter Pater's fiction, which presents the critic with numerous causes of frustration, not the least of which is a lack of both dramatic narration and description. Pater is rarely vivid and firsthand in his fiction; he tends instead toward exposition. Monsman's emphasis in Pater's Portraits is "tracing out" the conscious artistic structure of Pater's fiction. The scope of Pater's writings comprises nothing less than Western culture itself; its subject is all that man has written, thought, said, sung, hoped, or prayed as a civilized creature over two and one-half millennia. Pater's success in handling such panoply is attributable to his discovery of a coherent pattern by which art, religion, and life can be organized. Monsman aims to discover in Pater's fiction the use of old scientific-religious patterns of myth to explain moments of religious and cultural awakening, to reveal the way in which one man arrived at a credo that would answer to the desolation of life and culture.